Penerapan Model Pembelajaran Mind Mapping untuk Meningkatkan Aktivitas Belajar Peserta Didik kelas V - Nurhikmah; Abdul Hakim; Nur Ilmi (STKIP Andi Matappa Pangkep, 2024)
This research is the application of the mind mapping learning model to improve the learning activities of class V students which aims to improve the learning process and activities of students in the Pancasila education subject. The type of research used is Classroom Action Research (PTK) with a qualitative approach. The subjects studied in this study were 26 people consisting of 11 men, 14 women, and 1 teacher. Data collection was carried out by observation, documentation, and questionnaire techniques. The data was analyzed using data condensation techniques, data presentation, and conclusion drawn. In the first cycle, the results showed that the learning process was in the sufficient category (C) and the learning activities of students were in the active learning activity category with a percentage of 78.4%. The second cycle shows that the learning process is in the good category (B) and the learning activities of students are in the category of very active learning activities with a percentage of 91.8%. The conclusion of this study is that the application of the mind mapping learning model can improve the learning process and activities of students in class V UPTD SD Negeri 62 Parepare.